Mercury content in woody biomass and its removal in the torrefaction process. (December 2020) - Dziok, Tadeusz; Kołodziejska, Ewa K.; Kołodziejska, Elżbieta L.
Abstract: Anthropogenic mercury emissions can be reduced by using biomass. However, the mercury content in the biomass varies within a relatively wide range and can be even higher than in coal. This especially relates to waste biomass, including wood residues. In some cases, its use may result in increased emissions. A solution may be subjecting the woody biomass to the torrefaction process before its utilisation. In the paper, samples of woody biomass derived from different parts of a tree were analysed: wood, bark, branches, leaves, needles and roots. The performed studies showed significant differences in mercury content: wood 0.8–5.7 μg kg −1, roots 1.9–6.5 μg kg −1, branches 1.2–10.3 μg kg −1, bark 6.0–43.5 μg kg −1, needles 19.8–29.6 μg kg −1, leaves 40.3–67.3 μg kg −1 (on dry basis). The torrefaction process allowed for a reduction of the mercury content in the woody biomass regardless of the part of the tree from which it was obtained. The effectiveness of mercury removal at 300 °C was between 83 and 99%, with an average of 90%. In light of the results obtained, torrefied biomass should be classified as a very low mercury fuel, below 0.3 μg MJ −1 . Highlights: Mercury content in the woody biomass varies within a relatively wide range. The torrefaction process allowed for a reduction of the mercury content in biomass. Torrefied biomass is a low mercury fuel. Anthropogenic mercury emissions can be reduced by using biomass.